The Effectiveness of the Triangle Passing Method on Soccer Passing Learning Outcomes - Muhammad Virgiawan Listanto; Vina Rohmatul Ummah (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study was motivated by the low soccer passing skills among elementary school students and the need for more effective instructional methods in physical education learning. The study aimed to examine differences in the improvement of soccer passing learning outcomes between students taught using the Triangle Passing method and those taught using conventional methods. The research employed a quantitative approach with an experimental method using a pretest–posttest control group design. The sample consisted of 88 students divided into an experimental group (n = 44) and a control group (n = 44). Data were collected through a soccer passing skills test and analyzed using paired sample t-tests and independent sample t-tests. The findings revealed that both groups experienced improvements in average scores. The experimental group improved from 23.93 to 28.29, while the control group improved from 23.06 to 26.54. However, the difference test indicated no significant difference between the two groups (p = 0.136 > 0.05). These findings indicate that both the Triangle Passing method and conventional methods were able to improve students’ passing skills, but the Triangle Passing method did not produce a significantly greater effect compared to the conventional method. This study implies that the effectiveness of sports skill learning methods should consider student characteristics, training intensity, and the duration of instructional implementation.